A TECHNIQUES OF DURIAN (Durio zibethinus L.) PROPAGATION VEGETATIVE: TEKNIK PERBANYAKAN TANAMAN DURIAN (Durio zibethinus L.) SECARA VEGETATIF - Zainal Abidin Zainal; Mundjanah Mundjanah (Universitas Muhammadiyah Sorong, 2023)
Durian is a fruit that has a distinctive aroma and bioactive compounds that are beneficial for human health. This study aimed to study the effect of various vegetative propagation techniques on the success of durian plant propagation. The research design used was a non-factorial randomized block design (RAK) with three treatments and five replications. The vegetative propagation technique using wedge grafting had a significant effect on the time of shoot emergence and the number of tillers, while insertion grafting had a significant effect on seedling height. From these three treatments, it is recommended to use shoot grafting treatment for durian plant propagation.